RESISTIVITY RESPONSE AND TIME DOMAIN INDUCED POLARIZATION IN THIN LAYER RESERVOIR PHYSICAL MODEL - BRIANNI PUTERI (NIM : 20214012), LULU
Thin layer reservoir plays an important role in the production of petroleum and natural gas fields, including in the area of fan deltas, alluvial, distributed channel, fracture basement, and turbidite. Hence characterization of thin layer become important and it is necessary to develop measurement techniques to characterized the thin layers. Thin layer is defined as a layer that have a thickness less than distance between potential probe. Induced Polarization and Resistivity are several techniques or methods in thin layer characterizing. Resistivity method is used to investigate and predict the characteristics of the subsurface of the earth by using electrical properties such as electricity. Induced polarization method (IP) is an electrical energy storage phenomenon in porous media. This principle works by flowing an electric current into the earth and then observing the potential difference that occurs after power has been removed. Ideally for medium without capacitance, the potential difference is zero. In the other hand if a particular medium do have capacitance, the potential difference is not zero. Measurement methods of the resistivity and IP were performed in the frequency domain and time domain. In this research, time domain is used to measure the effects of the chargeability and resistivity responses of the shale, kaolinite and sand that are arranged in series. Shale, kaolinite and sand kept wet and under controlled humidity condition. The experimental was design by varying the thickness of the rocks, while the total length and total volume was constant. The observation was conduct to seek the effect of the thickness from shale, kaolinite and sand per distance unit where the thickness between shale-sand and kaolinite-sand are same to the resistivity response and chargeability. Then, the effect of sand thickness changes per distance unit where the thickness between shale-sand and kaolinite-sand are different to the resistivity response and chargeability. Last is current polarity changes effect to resistivity response and chargeability. The result showed, if the thickness of shale-sand and kaolinite-sand are same there was no relation to their resistivity response, but if the thickness of shale-sand and kaolinite-sand are different and sand thickness changed, the resistivity response was increased.Chargeability response influenced by thickness changed per distance unit wether the thickness of shale-sand and kaolinite-sand are same or different. When the shale-sand and kaolinite-sand have the same thickness, chargeability was decreased, in the same time the thickness was increased. In other hand, when the shale-sand and kaolinite-sand thickness are different, chargeability was increased where in the same time the thickness was increased. Current polarity had an effect on the chargeability response, but did not have an effect on the resistivity response. Positive polarity gave the chargeability higher values than negative polarity.